Analisis Faktor-Faktor Visit Intention Pulau Morotai selama Pandemi COVID-19 - Hanipah; Shafira Nuraini; Chika Dwy Citra; Bagas Fiqri Kamil; Usep Suhud (Fakultas Ekonomi Universitas Negeri Jakarta, 2022)
This study examines the factors that influence the intention to visit Morotai Island during the COVID-19 pandemic. There are six variables used to measure, namely country image, destination image, travel motivation, tourist satisfaction, electronic word of mouth (E-WoM), and visit intention. For this reason, we use the research method of distributing questionnaires with the population in the study being people in Jakarta and using a sample of respondents who have the intention to visit Morotai Island with a vulnerable age of 25 years or more and involving 217 respondents who participated in filling out the questionnaire. The data is processed using exploratory factor analysis and a structural equation model. The result is that E-WoM affects the destination image. Penelitian ini mengkaji factor-faktor yang mempengaruhi niat berkunjung ke Pulau Morotai selama pandemic COVID-19. Ada enam variabel yang digunakan untuk mengukur, yaitu country image, destination image, travel motivation, tourist satisfaction, electronic word of mouth (E-WoM) dan visit intention. Untuk itu kami menggunakan metode penelitian menyebar kuesioner dengan populasi dalam penelitian ialah masyarakat di Jakarta dan menggunakan sampel responden yang memiliki niat untuk mengunjungi Pulau Morotai dengan rentan usia 25 tahun atau lebih dan mwlibatkan 217 responden yang ikut berpartisipasi mengisi kuesioner. Data diolah menggunakan explaratory factor analysis dan structural equation model. Hasilnya E-WoM mempengaruhi destination image.